A ciência é a alma do negócio: apropriações do discurso científico em propagandas de medicamentos contra a sífilis (Paraíba, 1932-1942) (Ágora Journal, 2021)
In this work, we analyze the appropriation of images and discourses associated with the social representation of science as a marketing strategy in the ads for syphilis drugs. Our focus of discussion is the advertisements published by the journal Medicina, official journal of the Society of Medicine and Surgery of Paraíba that circulated between the years 1932 and 1942. Emerged as an unfolding of the process of institutionalization of scientific medicine in the state from the 1920's on, Medicina was responsible for building a network of science circulation that connected doctors and readers of Paraíba to national and international production. To discuss these and other issues, we analyzed the advertising of drugs against syphilis in the Editions of the magazine Medicina based on studies by Ludwin Fleck and Sérgio Carrara on the structuring of syphilis concept and its relationship with the developmente of medical-scientific knowledge.
Keywords: History of medicine; Publicity; Syphilis